2004
DOI: 10.1084/jem.20031858
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Cytokine-induced Antiapoptotic Molecule Anamorsin Essential for Definitive Hematopoiesis

Abstract: Many growth factors and cytokines prevent apoptosis. Using an expression cloning method, we identified a novel antiapoptotic molecule named Anamorsin, which does not show any homology to known apoptosis regulatory molecules such as Bcl-2 family, caspase family, or signal transduction molecules. The expression of Anamorsin was completely dependent on stimulation with growth factors such as interleukin 3, stem cell factor, and thrombopoietin in factor-dependent hematopoietic cell lines, and forced expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 48 publications
3
119
1
Order By: Relevance
“…Although the molecular targets of the electron transfer flow generated by this protein-protein complex are not yet defined, suggestions for the targets of the electron flow include the conversion of the sulfur of cysteine (formally S 0 ) to the sulfide (S 2− ) present in Fe/S clusters and/or the reductive coupling of two [2Fe-2S] clusters to form a [4Fe-4S] cluster (13). This nondissociative electron transfer process might also rationalize how anamorsin regulates cell survival/death mechanisms in human cells (35) and why a stable Dre2-Tah18 interaction is essential for yeast viability (16). Indeed, the disruption of the stable interaction between anamorsin and Ndor1 might provoke the interruption of the electron flow between the two proteins within the cell and, as a result of that, its essential function for cellular survival is abolished and consequently cell death mechanisms might be activated.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular targets of the electron transfer flow generated by this protein-protein complex are not yet defined, suggestions for the targets of the electron flow include the conversion of the sulfur of cysteine (formally S 0 ) to the sulfide (S 2− ) present in Fe/S clusters and/or the reductive coupling of two [2Fe-2S] clusters to form a [4Fe-4S] cluster (13). This nondissociative electron transfer process might also rationalize how anamorsin regulates cell survival/death mechanisms in human cells (35) and why a stable Dre2-Tah18 interaction is essential for yeast viability (16). Indeed, the disruption of the stable interaction between anamorsin and Ndor1 might provoke the interruption of the electron flow between the two proteins within the cell and, as a result of that, its essential function for cellular survival is abolished and consequently cell death mechanisms might be activated.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine-induced apoptosis inhibitor 1 (CIAPIN1) is an important regulator of cell apoptosis. It has a significant inhibitory effect on multiple links in cell apoptotic pathways and a positive regulatory effect on Ras and other survival signaling pathways, thus promoting cell survival and proliferation (Shibayama et al, 2004). In recent years, many studies on the relationship www.intechopen.com between CIAPIN1 and tumor formation showed that CIAPIN1 expression was increased significantly in HCC, gastric cancer and other malignant tumor tissues (Ida et al, 2007;.…”
Section: Cytokine-induced Apoptosis-inhibiting Moleculementioning
confidence: 99%
“…4 Additionally, CIAPIN1 protects Ba/F3 cells against etoposide, gamma radiation and stauroporine in vitro. 4 In addition, our previous study confirmed that CIAPIN1 was upregulated in several multidrug resistance cancer cell lines and might have a role in mediating multidrug resistance of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…4 Additionally, CIAPIN1 protects Ba/F3 cells against etoposide, gamma radiation and stauroporine in vitro. 4 In addition, our previous study confirmed that CIAPIN1 was upregulated in several multidrug resistance cancer cell lines and might have a role in mediating multidrug resistance of cancer cells. 5,6 Furthermore, CIAPIN1 expression was correlated with malignant phenotype of several cancers such as gastric cancer, liver cancer, esophagus cancer, lung cancer, lymphoma and kidney cancer, 7--15 which strongly suggested that CIAPIN1 might be an important protein involving in tumorigenicity and carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%